Kinetic and molecular orbital analyses of dicarboxylic acylcarnitine methylesterification show that derivatization may affect the screening of newborns by tandem mass spectrometry. Issue 1 (1st January 2016) - Maeda, Yasuhiro; Nakajima, Yoko; Gotoh, Kana; Hotta, Yuji; Kataoka, Tomoya; Sugiyama, Naruji; Shirai, Naohiro; Ito, Tetsuya; Kimura, Kazunori
Graphical abstract: Abstract: Newborns are routinely screened for organic acidemias by acylcarnitine analysis. We previously reported the partial catalytic methylesterification of dicarboxylic acylcarnitines by benzenesulfonic acid moiety in the solid extraction cartridge during extraction from serum. Since the diagnosis of organic acidemias by tandem mass spectrometry is affected by the higher molecular weight of these derivatized acylcarnitines, we investigated the methylesterification conditions. The kinetic constants for the methylesterification of carboxyl groups on the acyl and carnitine sides of carnitine were 2.5 and 0.24 h −1, respectively. The physical basis underlying this difference in methylesterification rates was clarified theoretically, illustrating that methylesterification during extraction proceeds easily and must be prevented.